2020
DOI: 10.1155/2020/8821181
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Immunoassay for the Detection of Amyloid Beta 1-42 and Its Application in Urine Samples

Abstract: Amyloid beta peptides (Aβ1-42) have been found to be associated with the cause of Alzheimer’s disease (AD) and dementia. Currently, methods for detecting Aβ1-42 are complicated and expensive. The present study is aimed at developing an indirect competitive enzyme-linked immunosorbent assay (ic-ELISA) to detect Aβ1-42 by using a polyclonal antibody from alpaca, an application used in urine samples. The serum was collected from the alpaca after immunizing it with Aβ1-42 at 500 μg/injection 5 times. The ic-ELISA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…The study showed major advantages, including a significant decrease in average analytical time and high specificity to the target [14] . According to Wongta, Hongsibsong [50] , the development of an immunoassay can be applied to detect amyloid beta peptides (A β 1–42), which are related to Alzheimer's disease (AD) and dementia, and it provides an alternative method to diagnose high-risk and early stages of AD with rapid and simple analysis. This method is related to the binding activity between the antibody and the antigen or analyte using enzyme-linked immunosorbent assays (ELISAs) [ 18 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study showed major advantages, including a significant decrease in average analytical time and high specificity to the target [14] . According to Wongta, Hongsibsong [50] , the development of an immunoassay can be applied to detect amyloid beta peptides (A β 1–42), which are related to Alzheimer's disease (AD) and dementia, and it provides an alternative method to diagnose high-risk and early stages of AD with rapid and simple analysis. This method is related to the binding activity between the antibody and the antigen or analyte using enzyme-linked immunosorbent assays (ELISAs) [ 18 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, recent research efforts have focused on the discovery of novel biomarkers, eventually including personalized markers, for assessing onset and/or progression of neurodegenerative diseases [1,8,135]; diagnostic and/or prognostic biomarkers are especially needed in the area of synucleinopathies [14]. Moreover, much research has been recently directed toward developing improved analytical methods for reliable measurement of established biomarkers, each one alone or often in combination, in easily available biological fluids, such as plasma, urine, or saliva [1,[136][137][138]. Success in the discovery of novel biomarkers and development of highly reliable and easy to perform methods for biomarker analysis will definitely facilitate the evaluation of candidate peptide-based vaccines for neurodegenerative diseases and accelerate further progress.…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal α-syn(1-10) and C-terminal α-syn (90-140) fragments were found to be exposed with ELISA experiments [101]. On the other hand, the C-terminal epitopes α-syn(111-140)/α-syn (121)(122)(123)(124)(125)(126)(127)(128)(129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140) were recognized by human anti-α-syn antibodies isolated from PD patients [102]. Moreover, the secondary structural features of α-syn in an aqueous environment have been studied with computer simulation [103].…”
Section: Peptide Epitopes Used In α-Syn Vaccinesmentioning
confidence: 99%
“…Currently, most measurements of Aβ 42 rely on immunoassay techniques, such as enzyme-linked immunoassays [40][41][42], which are time consuming. Various techniques have been attempted for the probing of Aβ 42 , such as resonance light scattering [43], surface-enhanced Raman spectroscopy (SERS) [44], and localized surface plasmon resonance (LSPR) [45,46], but these are less flexible, costly, and labour-intensive, requiring complex equipment.…”
Section: Introductionmentioning
confidence: 99%